Tunable Aggregation‐Induced Emission of Tetraphenylethylene via Short Peptide‐Directed Self‐Assembly. Issue 1 (6th May 2016) - Liu, Kai; Zhang, Ruiyun; Li, Yongxin; Jiao, Tifeng; Ding, Dan; Yan, Xuehai
Abstract : Tunable aggregation‐induced emission of tetraphenylethylene is well realized via short peptide‐directed self‐assembly associated with synergy of noncovalent intermolecular interactions, including electrostatic, hydrophobic, and π–π interactions. Cationic diphenylalanine can enhance the fluorescence signal of tetraphenylethylene (TPE) nanoparticles, while 9‐fluorenylmethoxycarbonyl‐l ‐Lysine can weaken the emission of TPE nanoparticles.